Paper-based and computer-based admission tests for medicine – are they equivalent? - Escher, Malvin; Weppert, Daniel; Amelung, Dorothee; Huelmann, Thorben; Stegt, Stephan; Hissbach, Johanna (Frontiers in Education, 2023)
Admission tests are among the most widespread and effective criteria for student selection in medicine in Germany. As such, the Test for Medical Studies (TMS) and the Hamburg Assessment Test for Medicine, Natural Sciences (HAM-Nat) are two major selection instruments assessing applicants’ discipline-specific knowledge and cognitive abilities. Both are currently administered in a paper-based format and taken by a majority of approximately 40,000 medicine applicants under high-stakes conditions yearly. Computer-based formats have not yet been used in the high-stakes setting, although this format may optimize student selection processes substantially. For an effective transition to computer-based testing, the test formats’ equivalence (i.e., measurement invariance) is an essential prerequisite. The present study examines measurement invariance across test formats for both the TMS and HAM-Nat. Results are derived from a large, representative sample of university applicants in Germany. Measurement invariance was examined via multiple-group confirmatory factor analysis. Analyses demonstrated partial scalar invariance for both admission tests indicating initial evidence of equivalence across test formats. Generalizability of the results is examined and implications for the transition to computer-based testing are discussed.